A major role for Nrf2 transcription factors in cell transformation by KSHV encoded oncogenes - Sapochnik, Daiana; Raimondi, Ana R.; Medina, Victoria; Naipauer, Julian; Mesri, Enrique A.; Coso, Omar (Frontiers in Oncology, 2022)
Kaposi's sarcoma (KS) is the most common tumor in AIDS patients and the highly vascularized patient's skin lesions are composed of the cells that derive from the endothelial tissue transformed by the KSHV virus. Heme oxygenase-1 (HO-1) is an enzyme upregulated by the Kaposi´s sarcoma-associated herpesvirus (KSHV) and highly expressed in human Kaposi Sarcoma (KS) lesions. The oncogenic G protein-coupled receptor (KSHV-GPCR or vGPCR) is expressed by the viral genome in infected cells and is involved in KS development, HO-1 expression and vascular endothelial growth factor (VEGF) expression. vGPCR induces HO-1 expression and HO-1 dependent transformation through the Ga13 subunit of heterotrimeric G proteins and the small GTPase RhoA. We have found here several lines of evidence that support a role for Nrf2 transcription factors and family members in the vGPCR-Ga13-RhoA signaling pathway that converges on the HO-1 gene promoter. Our current information assigns a major role to ERK1/2MAPK pathways as intermediates in signaling from vGPCR to Nrf2, influencing Nrf2 translocation to the cell nucleus, Nrf2 transactivation activity and consequently HO-1 expression. Experiments in nude mice show that the tumorigenic effect of vGPCR is dependent on Nrf2, and in the context of complete KSHV genome, we show that the lack of vGPCR induced an increase cytoplasmic localization of Nrf2 correlated with a downregulation of HO-1 expression. Moreover, we also found an increase of phospho-Nrf2 nuclear localization in mouse KS-like KSHV (positive) tumors when compared to KSHV (negative) mouse KS-like tumors. Our data highlights the fundamental role of Nrf2 linking vGPCR signaling to the HO-1 promoter acting upon not only HO-1 gene expression regulation but also in the tumorigenesis induced by vGPCR. All in all these data pinpoints this transcription factor or its associated proteins as putative pharmacological or therapeutic targets in KS.